Periodontal Changes in Conjunct Prostheses - Valeria Pendefunda; Arina Ciocan-Pendefunda; Carmen Pirlia (Romanian Society of Oral Rehabilitation, 2010)
Introduction. The treatment of reduced partially edentulous patients with gnatprosthetic bridges, linked to the organic substructure, determines on the gum¡¦s tissue many adaptive changes, related to the following factors: previous state of sulcular epithelium, quality of the finishing edges of the microprostheses, material from which the bridge is made, definitive cementing materials, etc. The aim of our study is to assess the impact of the fixed prostheses upon the periodontal health. Material and method. The study includes 112 patients (54 males and 58 females) with ages between 20-60 years. The evaluation was made on 282 conjunct prostheses. The statistical processing was made by the program STATISTIC (dedicated to medical research) and specific tests as ANOVA, Spjotvol/Stoline, Pearson, CHI ¡V square (ƒÓ2), Fisher, Spearman, etc. Results. Periodontal changes appeared in 44.64% of cases. This aspect was correlated with different particularities of the prosthetic device. These can be taken into consideration as potential risk factors for periodontal changes. The study of periodontal health, related to the material that was used, showed a low prevalence in metal ceramic bridges (14.3%) and metal composite bridges (8.9%). Periodontal changes are more important in case of high amplitude and older bridges, and they are influenced by the material and the quality of their finishing. Although, there is a correlation between oral hygiene and periodontal changes of the prosthetic bridges patients. Conclusions. Results show a close relation between periodontal changes and: the amplitude and age of the prosthetic bridges, quality of the finishing edges of the microprostheses, surface texture, axial and transversal adjustment and the materials used for the bridge and final cementation.